Adam King: a man for all seasons. (November 2015) - McOmish, David
<x content-type="archive" xml:space="preserve">Abstract</x> Adam King was born into a respectable family of advocates on the eve of the Scottish Reformation. He was a professor of mathematics and philosophy at the University of Paris for many years, who then returned to Scotland to become an advocate and commissary of Edinburgh. His family's adherence to the Catholic faith in the immediate aftermath of the Reformation was overt and vigorous, and led to significant disruption in their lives. This article charts the life and career of Adam through these turbulent times, from his battles with religious authorities to his emergence as a man with significant influence in post-reformation Scotland. It provides a preliminary map of his friends and acquaintances, and presents evidence that they reflect a strong literary and scientific culture in early modern Scotland, which transcended their religious affiliations and was addressing some of the most pressing questions raised by the Scientific Revolution.